Evaluating Social Complexity and Inequality in the Balkans Between 6500 and 4200 BC - Porčić, Marko (Journal of archaeological research, 2019)
The subject of this paper is the social structure and sociocultural evolution of Balkan Neolithic and Eneolithic societies between 6500 and 4200 BC. I draw on archaeological evidence from three major regions of the Balkans related to demography, settlement, economy, warfare, and differences in status and wealth between individuals and groups to evaluate the degree and kind of social complexity and inequality. The trend in these data is of increase in social complexity and inequality over two millennia following the introduction of agriculture to the Balkans, as the simple and small hamlets of the late seventh and early sixth millennia transformed into large villages and tell sites of the late sixth and fifth millennia, in parallel with the development of copper metallurgy and regional exchange networks. There is no evidence of social stratification or the formation of complex systems of regional integration such as (proto)states or urban centers. The Balkan communities of this period were essentially village communities with social inequalities, when present, limited to differences in prestige and potentially rank.